National government measures related to COVID-19 in Argentina: vulnerable populations, participation and mental health - C. Bang; B. Misischia; M. Ussher; M. M. Bottinelli; M. Nabergoi; G. Granja (Ибероамериканские тетради, 2022)
In March 2020, the first case of coronavirus was registered in Argentina and care measures were adopted. From different spaces, research initiatives emerged addressing various problems related to this pandemic. In this framework, a working group was formed to develop a network research project: “COVID-19, Health and social protection: contributions from territorial care practices for the strengthening of comprehensive community mental health policies in the new postpandemic scenarios.” Its main objective is to describe the practices and experiences of health/mental health care developed by territorial actors, analyzing their articulation with government measures during the year 2020. The methodology used is exploratory descriptive, founded on the triangulation of sources, instruments and qualitative quantitative indicators, based on the systematization of practices and experiences of territorial actors and the analysis of their relationship with national, provincial and local public policies.Various publications indicate that populations in situation of vulnerability are more exposed in relation to their health/mental health and it has also been analyzed that social participation is a central component in Community Health and constitutes, in cases of greater vulnerability, a condition to ensure survival.This article characterizes the national government measures related to COVID-19 in Argentina, with respect to these populations, and analyzes those that make explicit reference to social participation.